School zoning policy as a form of implication of the 5th precepts of pancasila - Nadya Khairani Afiefa; Siti Liyanawati (Institute of Computer Science (IOCS), 2023)
The implementation of the school zoning policy has generated pros and cons related to the realization of educational equality in Indonesian society, which adheres closely to Pancasila as a guide to life. This research aims to find out whether the zoning policy implemented by the Indonesian government has referred to and is in accordance with the implementation of the 5th precept of Pancasila. Furthermore, this research is a qualitative research with literature study method. The data collection technique begins with verifying by comparing the data that has been collected. After that the data is categorized and sorted according to the research focus. Then the data that has been grouped is analyzed to make a deeper interpretation related to the problems in the research conducted. Furthermore, the data is reduced by selecting more detail, detail and selectively. Then the data that has been selected is presented by conveying it through the analysis process first. After that the researcher draws conclusions based on the data analysis that has been carried out. Based on the results of the research that has been conducted, it can be concluded that (1) The zoning policy established by the government is a means of equitable distribution of the quality of education (2) The zoning policy provides opportunities for citizens to enter the nearest formal education level (3) The zoning policy as an implication of practicing the 5th precept makes every school provide quality education services without discriminating.